Hubungan Asupan Zat Besi Dan Kadar Hemoglobin Dengan Kesegaran Jasmani Pada remaja Putri Di SMA N 1 Polokarto Kabupaten Sukoharjo - Dwiati, Aulia Pretty Martia; , Muwakhidah, SKM, M.Kes; , Wahyuni, SKM., M.Kes (2016)
Physical fitness is needed for daily activities. Someone with a good physical fitness, the effectiveness and productivity can be maintained or increased. The intake of iron and the level of hemoglobin are factors that influence physical fitness. The precentage of anemic in senior high school of Polokarto was 60% in 2014. To determine the relationship between iron intake and hemoglobin level with physical fitness in female adolescent at Senior High School of Polokarto, Sukoharjo. This study was an obsevational with cross-sectional approach and the subjects were 68 students whom chosen by purposive random sampling from 10th and 11th grade students. Data an iron intake were obtained using semi quantitative food frequencies. The hemoglobin levels was measured using cyanmethhaemoglobin method, whereas physical fitness level was measured using harvard step test. This research showed that there were 52 subjects (76,4%) categorized as having low iron intake. Whereas there were 37 subjects who were (54,4%) anemic. There were 37 subjects (54,4%) who had low physical fitness. Simple regression analysis showed that iron intake contributed 31,9% variant to physical fitness level. Whereas hemoglobin level contributed 15,2% variant to physical fitness. There was a relationship between iron intake and physical fitness (p=0,0001) and there was a relationship between hemoglobin level and physcal fitness (p=0,001). Keyword : iron intake, hemoglobin level, physical fitness Bibliography : 46 (1997-2014)